Nontargeted and targeted metabolomics analysis provides novel insight into nonvolatile metabolites in Jianghua Kucha tea germplasm (Camellia sinensis var. Assamica cv. Jianghua) - Wenliang Wu; Meiling Lu; Jiakun Peng; Haipeng Lv; Jiang Shi; Shuguang Zhang; Zhen Liu; Jihua Duan; Dan Chen; Weidong Dai; Zhi Lin (Food Chemistry: X, 2022)
Jianghua Kucha (JHKC) is a special tea germplasm with high bitterness growing in China; however, the chemical characteristics of JHKC are not completely understood. In this study, 61 differential metabolites were identified between 11 wild JHKC individuals and 3 control cultivars of Fudingdabai, Yunkang 10, and Zhuyeqi using comprehensive nontargeted and targeted metabolomics approach. The JHKC accessions mainly possessed significantly higher levels of purine alkaloids of theacrine (12.06 ± 5.23 mg/g) and 1,3,7-trimethyluric acid, non-epi-form flavanols (catechin, gallocatechin, catechin gallate, and gallocatechin gallate), and methylated flavanols of epigallocatechin-3-O-(3″-O-methyl)-gallate (4.79 ± 1.45 mg/g) and epicatechin-3-O-(3″-O-methyl)-gallate (1.02 ± 0.34 mg/g), as well as significantly lower levels of flavonol glycosides, which indicated that caffeine metabolism, flavonoid biosynthesis, and flavonol and flavone biosynthesis are mostly differential metabolic pathways. Our study demonstrated that JHKC germplasm is a promising resource for breeding novel tea cultivars with high contents of theacrine, non-epi-form flavanols, and methylated flavanols.